The Cult of Saints in Late Antiquity [online resource] - Ward-Perkins, B (University of Oxford, 2024)
The Cult of Saints in Late Antiquity database is making readily accessible and searchable the early evidence for the cult of Christian saints (up to around AD 700), with key texts presented in their original language, all with English translation and brief contextual commentary. Over 8,000 records, including over a thousand images of original sources, were originally compiled in a bespoke online database, and are now available on the Sustainable Digital Scholarship (SDS) platform. Funded by the European Research Council, this project created a complex database with thousands of records, including a complex set of metadata. Researchers and users can search the project using key information like dates, locations, forms of worship, and other keywords.